Water-based pole piece edge sealing insulating adhesive, preparation method and application
By using aqueous pole edge sealing insulating adhesive in lithium-ion batteries, using core-shell emulsion polymerization technology and specific monomer ratios, the short circuit problem caused by the shrinkage of the separator under high temperature conditions and the problem of insufficient adhesive strength of the insulating coating is solved, and a battery insulating coating with high temperature stability and environmental protection is achieved.
Patent Information
- Application Number
- CN202411701152.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-14
AI Technical Summary
The existing lithium-ion battery separators shrink under high temperature conditions, resulting in short-circuit contact between positive and negative electrodes, and the adhesive force of the insulating coating is weak and easy to lose powder, which cannot effectively avoid the risk of short-circuiting of the battery during accidental impact or extrusion. At the same time, traditional solvent-based adhesives have problems of environmental pollution and high costs.
The aqueous polar sheet edge sealing insulating adhesive is used, and through core-shell emulsion polymerization technology, a multi-layer structural adhesive with polyacrylic acid and its esters as the core and PAA polymer structural fragments as the shell is designed to control the proportion of polar groups and acrylic esters, and improve the toughness and electrolyte resistance of the adhesive.
The adhesive is stable in high temperature and electrolyte, which improves the insulation performance and safety of the battery pole sheet, reduces production costs, and meets environmental protection requirements.
Smart Images

Figure BDA0005153336820000051 
Figure BDA0005153336820000061 
Figure BDA0005153336820000062
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adhesive materials, and in particular relates to a water-based electrode edge sealing insulating adhesive, a preparation method and an application thereof. Background Art
[0002] Lithium-ion batteries have been widely used in mobile phones, power tools, energy storage and electric vehicles due to their high specific energy, long cycle life, low self-discharge, no memory effect and environmental protection. However, with the demand for high specific energy and super fast charging, battery safety has received more and more attention.
[0003] Lithium-ion batteries are mainly composed of materials such as positive electrodes, negative electrodes, electrolytes and diaphragms. The diaphragm is located between the positive and negative electrodes. Its main function is to separate the active substances of the positive and negative electrodes to prevent the positive and negative electrodes from directly contacting and short-circuiting. However, the diaphragms currently used are mainly polyolefin diaphragms and ceramic diaphragms with polyolefin diaphragms as base films. The melting temperature of polyethylene diaphragms is about 135°C, and the melting temperature of polypropylene diaphragms is about 165°C. Even if the heat resistance of ceramic diaphragms is improved to a certain extent, under high temperature conditions, the diaphragm will also shrink, resulting in a short circuit between the positive and negative electrodes, creating a safety risk. In addition, due to the low mechanical strength of the diaphragm, when the battery is accidentally hit or squeezed, the exposed edges of the pole pieces are prone to contact and short circuit, which is also an important safety hazard for the battery.
[0004] Therefore, at this stage, when preparing the positive electrode, battery manufacturers apply a layer of insulating coating on the bare foil at the edge of the pole piece to effectively avoid the risk of short circuit caused by diaphragm shrinkage or battery deformation. However, the ceramic coating prepared by the current insulating coating products has high hardness, weak adhesion, and is easy to lose powder. After being soaked in the electrolyte, it is easy to fall off and lose its function. At the same time, the product used is also a solvent-based PVDF adhesive. In addition to its high cost and toxic pollution to the environment, the use of fluoride is also restricted by environmental protection policies. Therefore, it is urgent to develop an environmentally friendly coating adhesive with strong adhesion, high toughness and strength, and excellent electrolyte tolerance to improve the safety, environmental protection and low cost of lithium batteries.
[0005] To this end, the Chinese invention patent with application number CN2002210960967.9 discloses a polymer insulating coating and its preparation method, specifically disclosing a polymer insulating coating prepared by using aramid fiber and its derivatives as the first polymer, using one or more of polyimide, polyacrylonitrile, polyacrylate, polyvinylidene fluoride, and polytetrafluoroethylene as the second polymer, using a crosslinker solution to modify the first polymer, and then mixing and stirring with the second polymer; however, the above coating needs to be dissolved in an organic solvent, and the volatilization of the solvent in the subsequent curing process will have an impact on the environment. If the solvent is recovered, the complexity of the preparation process and the production cost will be increased; and the raw materials contain fluorine-containing substances such as polyvinylidene fluoride and polytetrafluoroethylene, which cannot fully meet environmental protection requirements. The insulating edge coating adhesives used for substitution are currently also a research hotspot in the field of new energy. However, since the insulating edge coating adhesive works in an electrolyte immersion environment and has to withstand high and low temperature and high frequency vibration tests, the attached substrate is aluminum foil and copper foil that are difficult to adhere to, and it also needs to withstand a strong redox reaction environment, so the technical difficulty of development is very large. At present, there are no reports and applications of PAA insulating edge coating products.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] The purpose of the present invention is to provide a water-based electrode edge sealing insulating adhesive to address the problems in the above-mentioned prior art. By controlling the proportion of various monomers and self-emulsifying groups in the adhesive, it exhibits excellent bonding and wetting properties for the current collector aluminum foil and meets various technical requirements in the working environment of lithium batteries.
[0008] On the other hand, the present invention provides a method for preparing a water-based electrode edge sealing insulating adhesive, which adopts a core-shell emulsion polymerization method to prepare a specially designed polyacrylic acid and its ester as a core, a PAA polymer structure fragment with specific functions as a single or multi-layer shell, and a three-dimensional network structure is completed by cross-linking monomers, thereby improving the electrolyte tolerance performance of the adhesive; and the product uses water as a solvent, does not need to recover the solvent, is environmentally friendly and low-carbon, simplifies the preparation steps and application process, and reduces the production cost.
[0009] On the other hand, the present invention provides an application of a water-based insulating adhesive for edge sealing of pole pieces. Since the adhesive has excellent electrolyte tolerance, the prepared insulating slurry will not dissolve or swell due to long-term immersion in electrolyte when used as the insulating edge sealing of the bare foil part of the pole piece current collector, thereby protecting the pole piece from corrosion, being beneficial to maintaining the battery size, having high bonding reliability, and extending the battery life.
[0010] In order to achieve the above-mentioned object, the first aspect of the present invention provides a water-based electrode edge sealing insulating adhesive, which has polyacrylic acid and its ester as the core, PAA polymer structure fragment as the single-layer or multi-layer shell, and multiple monomers including acrylic acid, acrylic ester, styrene, polar monomer, self-emulsifying monomer, cross-linking monomer as raw materials, and is prepared by core-shell emulsion polymerization;
[0011] In the prepared water-based electrode edge sealing insulating adhesive, the polar group accounts for 5-30%; the self-emulsifying group accounts for 1-8%.
[0012] The polar group is selected from one or more combinations of carboxyl, cyano, hydroxyl, amine, amide, modified amide and sulfonic acid.
[0013] In a further solution, the carboxyl group content in the prepared water-based electrode edge sealing insulating adhesive is 5-20%.
[0014] Appropriate adhesion is crucial for the insulating adhesive for edge sealing of pole pieces, and the number of polar groups has a significant impact on the bonding performance. In order to ensure that the water-based insulating adhesive for edge sealing of pole pieces has appropriate adhesion, the proportion of polar groups is controlled to be 5-30%. Further considering the balance between the viscosity and bonding performance of the adhesive by the polar groups, by limiting the proportion of carboxyl-containing monomers in the polar groups to 5-20%, the bonding strength of the adhesive is ensured, the moisture absorption of the insulating coating is reduced, and the slurry made of the adhesive is ensured to have good fluidity and is suitable for high-speed transfer coating processes. In a further scheme, the self-emulsifying group includes a hydrophilic group and a hydrophobic group in the self-emulsifying monomer, and the proportion of the self-emulsifying group is used to represent the proportion of the self-emulsifying monomer.
[0015] Furthermore, in the water-based electrode edge sealing insulating adhesive, the proportion of acrylate is 20-50%, preferably 30-40%. Since the acrylate monomer is a soft monomer, the control of the proportion of the acrylate monomer is used to achieve the regulation of the Tg of the adhesive, significantly improving the toughness of the adhesive. Controlling the Tg of the adhesive at around 60°C can balance the mechanical properties and heat resistance of the adhesive, so that it can meet the use requirements of water-based electrode insulation bonding; and controlling the proportion of cross-linking monomers to 3-10% allows moderate cross-linking to occur in the adhesive, which is beneficial to maintaining the toughness of the adhesive while improving the electrolyte resistance.
[0016] The acrylic ester is selected from one or more combinations of isooctyl acrylate, hydroxyethyl acrylate, butyl acrylate and diallyl phthalate.
[0017] Furthermore, the polar monomers used to prepare the water-based electrode edge sealing insulating adhesive include a combination of one or more of acrylonitrile, acrylic acid, acrylamide, hydroxy acrylate, hydroxypropyl methacrylate, and vinyl polyether.
[0018] Furthermore, the polar monomer is selected from one or more combinations of acrylic acid, acrylonitrile, acrylamide, and hydroxyethyl acrylate.
[0019] Furthermore, the mass proportion of styrene is 2-7%.
[0020] Furthermore, the mass proportion of the cross-linking monomer is 3-10%, preferably 6-8%.
[0021] Furthermore, the cross-linking monomer is selected from at least one of diacetone acrylamide, oxalyl hydrazide, isobutoxy acrylamide, epoxy acrylate, methacryloxytrimethoxysilane, and diallyl phthalate.
[0022] The crosslinking monomers are preferably two, selected from the combination of diacetone acrylamide\ADH and isobutoxy acrylamide, diallyl phthalate and isobutoxy acrylamide, diacetone acrylamide and epoxy acrylate, or adipic dihydrazide and epoxy acrylate.
[0023] Furthermore, the self-emulsifying monomer is a carboxylate with a double bond, a sulfonate with a double bond and / or a polyether with a double bond.
[0024] Preferably, the self-emulsifying monomer is selected from at least one of acrylate, allyl polyoxyethylene sulfonate, vinyl polyoxyethylene sulfonate, allyl polyether and vinyl polyether.
[0025] Preferably, the self-emulsifying monomer is selected from at least one of acrylate, allyl polyoxyethylene sulfonate and vinyl polyether.
[0026] In the above scheme, polar groups such as carboxyl, cyano, hydroxyl, amide, and sulfonic acid groups are introduced into the adhesive by limiting the selection range of polar monomers, cross-linking monomers, and self-emulsifying monomers. The surface tension of the adhesive is designed and regulated by the selection of polar groups, so that the adhesive can fully wet the surface of the current collector and exhibit excellent wetting and bonding properties.
[0027] At the same time, the selection of self-emulsifying monomers avoids the use of small molecule emulsifiers. This is because small molecule emulsifiers can migrate into the electrolyte after the electrode is immersed in the electrolyte, causing damage to the battery performance. Self-emulsifying monomers are more beneficial to the battery performance than small molecule emulsifiers.
[0028] The second aspect of the present invention provides a method for preparing the above-mentioned water-based electrode edge sealing insulating adhesive, comprising the following steps:
[0029] S1. At a preset temperature, a part of acrylate, a part of polar monomer, a part of self-emulsifying monomer, a part of cross-linking monomer and water are emulsified at a high speed, and then emulsion polymerization is performed to obtain a core emulsion A;
[0030] S2, at a preset temperature, uniformly mix part of polar monomers, part of acrylates, another part of self-emulsifying monomers and another part of cross-linking monomers, and gradually dropwise react in the bottom water with emulsion A as the core to obtain a double-layer structure emulsion B;
[0031] S3, at a preset temperature, uniformly mix part of the polar monomer, the remaining part of the acrylate, and a small part of the self-emulsifying monomer, and gradually dropwise react in the bottom water with the emulsion B as the core to obtain a three-layer structure emulsion C;
[0032] The emulsion B or C is post-modulated to obtain a water-based electrode edge sealing insulating adhesive with a double-layer or multi-layer core-shell structure.
[0033] In the above scheme, the core emulsion A prepared by step S1 can be used as a seed emulsion to directly carry out shell polymerization, and the preparation steps are simple and easy to implement; since the selected cross-linking monomer can achieve cross-linking at a lower temperature, the use process requirements are relatively low, which is convenient for large-scale production and promotion.
[0034] The polymerization temperature is 80-86° C., and the emulsion polymerization is continuously carried out during steps S1, S2 and S3, with a stirring speed of 200-1000 rpm.
[0035] The post-treatment in step S2 or S3 includes: heat-preserving and aging the target emulsion at 86-90° C. for 2 hours, then cooling to 40° C., adjusting the pH of the emulsion to 7-7.5, and adding ADH to obtain a water-based electrode edge sealing insulating adhesive.
[0036] The consistency of the water-based electrode edge sealing insulating adhesive prepared by the above method is 100-1000cps.
[0037] The third aspect of the present invention provides the use of the above-mentioned water-based electrode edge sealing insulating adhesive for edge sealing bonding and coating of the bare foil portion of the current collector in the battery electrode.
[0038] Preferably, the inorganic filler can be dispersed efficiently to obtain a uniform and stable slurry, which is used for edge sealing and coating of the bare foil part of the current collector in the battery pole piece. The inorganic filler includes bohmite, calcium carbonate, and titanium dioxide.
[0039] The beneficial effects of the present invention are:
[0040] 1. In the water-based electrode insulating edge sealing adhesive provided by the present invention, polar groups such as carboxyl, cyano, hydroxyl, amino, and sulfonic acid groups are introduced into the adhesive system through the selection of raw material monomers and the control of the ratio of each monomer, and the surface tension of the adhesive is controlled by the design of specific polar groups; at the same time, the viscosity of the adhesive is adjusted by the ratio of each group in the polar group in the core or shell layer, so that the adhesive has excellent bonding and wetting properties to the current collector aluminum foil, and improves the bonding firmness and reliability. At the same time, it has good wetting, dispersion and bonding capabilities for inorganic fillers such as boehmite, titanium dioxide, and calcium carbonate, and has a wide range of applications and high application flexibility. The control of the surface tension of the adhesive designed in this patent also ensures the adaptability to oil stains on the surface of the aluminum foil. Generally, oily foil does not need to be degreased, and the coating of this product can obtain an insulating coating with excellent comprehensive performance.
[0041] 2. The water-based electrode insulation edge sealing adhesive provided by the present invention uses water as a solvent, replacing oily solvents such as NMP used in traditional adhesives. There is no need to recover the solvent, which simplifies the coating process. In addition, the adhesive system does not contain fluorine, which meets environmental protection requirements and future technological development trends, and has low production costs.
[0042] 3. Self-emulsifying monomers are used to replace traditional small molecule emulsifiers to prevent small molecule emulsifiers from remaining in the coating and migrating into the electrolyte, which will affect the battery performance. The use of multiple cross-linked monomers improves the adhesive's tolerance to the electrolyte. After the adhesive is formed into a film, the electrolyte absorption rate measured when immersed in an electrolyte at 60°C is low. It will not swell or dissolve due to long-term contact with the electrolyte, and will not affect the battery life.
[0043] 4. The core-shell emulsion polymerization method is used to obtain a shell structure with PAA as the core and polar monomers as the main components, which ensures the excellent storage stability, dispersion performance of the adhesive and the friction resistance of the adhesive layer formed on the surface of the current collector. DETAILED DESCRIPTION
[0044] Exemplary embodiments of the present invention will be described in more detail below. Those skilled in the art will appreciate that the following embodiments are only used to explain the technical principles of the present invention and are not intended to limit the protection scope of the present invention.
[0045] Evaluation or testing methods:
[0046] 1. Resistance to electrolyte wet friction (200 times):
[0047] Tested according to ISO 8251-87.
[0048] 2. Electrolyte absorption rate (60℃ / 24h):
[0049] After the adhesive film is dried and solidified, take 1-2g and soak it in a sealed bottle filled with electrolyte. Place the sealed bottle in a 60℃ constant temperature water bath. After 24 hours, take out the film, absorb the surface electrolyte with filter paper and weigh it. Calculate the percentage of weight increase after soaking.
[0050] 3. The test method for peeling force is:
[0051] Tape method: 3m test tape (model Scotch 600-Q33), 1 kg pressure pressed on the positive electrode coating surface, left naturally for 30 minutes; FBS-5D single-arm digital display tensile testing machine 180° peeling, take the average value of three samples.
[0052] Sample preparation conditions: lithium iron phosphate and conductive agent: glue (solid): water = 98:2:60, coating thickness 100-120 μm, the sample is baked at 120°C for 2 minutes and then placed in a drying dish for 24 hours before testing.
[0053] Embodiment 1
[0054] As an embodiment of the present invention, this embodiment provides a water-based electrode edge sealing insulating adhesive, and the weight percentage composition of the raw materials is as follows:
[0055]
[0056]
[0057] The specific preparation process is:
[0058] (1) 3% acrylic acid, 20% styrene, 8% acrylonitrile, 30% isooctyl acrylate, 5% allyl phthalate, 2% isobutoxyacrylamide, 1.5% allyl polyoxyethylene sulfonate, and 50% water are dispersed at a speed of 3000 r / min for 2 minutes to obtain a stable emulsion which is pumped into a high-level tank 1;
[0059] (2) Place the polymerization kettle in a constant temperature water bath at 82°C, add 2% ammonium bicarbonate and 100% water into the kettle;
[0060] (3) Dissolve 0.6% ammonium persulfate in 50% water and put it into the high-level tank 2;
[0061] (4) Add the monomers in the header tanks 1 and 2 to the polymerization kettle simultaneously, add the raw materials in header tank 1 at a constant speed over 30 minutes, and stop adding the raw materials in header tank 2 after half of the raw materials are added, and keep warm for 30 minutes;
[0062] (5) Mix the remaining raw materials together and pump them into high-level tank No. 1. At the same time, add the raw materials from high-level tanks No. 1 and 2 dropwise at a uniform rate. The addition will be completed within 30 minutes.
[0063] (6) Immediately raise the temperature to 88°C and keep warm for 1 hour;
[0064] (7) Cool down to 40°C, slowly add 10% sodium hydroxide and 50% water to form a solution, add all the solution over 10 minutes, stir for 30 minutes, and the obtained emulsion has a solid content of 33% and a consistency of 300 cps.
[0065] Embodiment 2
[0066] In parts by weight (parts), the raw material composition is as follows:
[0067]
[0068] The specific preparation process is:
[0069] (1) Dispersing 6% acrylic acid, 20% styrene, 2% hydroxyethyl acrylate, 35% isooctyl acrylate, 5% diacetone acrylamide, 2% isobutoxy acrylamide, 2% allyl polyoxyethylene sulfonate, and 50% water at a speed of 3000 r / min for 2 minutes to obtain a stable emulsion, which is pumped into a high-level tank 1;
[0070] (2) Place the polymerization kettle in a constant temperature water bath at 82°C, add 2% ammonium bicarbonate and 100% water into the kettle;
[0071] (3) Dissolve 0.6% ammonium persulfate in 50% water and put it into the high-level tank 2;
[0072] (4) Add the monomers in the header tanks 1 and 2 to the polymerization kettle simultaneously, add the raw materials in header tank 1 at a constant speed over 30 minutes, and stop adding the raw materials in header tank 2 after half of the raw materials are added, and keep warm for 30 minutes;
[0073] (5) Mix the remaining raw materials together and pump them into the No. 1 high-level tank. At the same time, add the raw materials from the No. 1 and No. 2 high-level tanks at a uniform rate. The addition is completed within 30 minutes.
[0074] (6) Immediately raise the temperature to 88°C and keep it for 1 hour;
[0075] (7) Cool down to 40°C, slowly add an emulsion of 10% sodium hydroxide and 30% water over 10 minutes, and stir for 30 minutes;
[0076] (8) Add a solution of 2.5% adipic dihydrazide and 20% water into the kettle at once and stir evenly to obtain an emulsion with a solid content of 32% and a consistency of 220 cps. A core-shell emulsion with excellent performance is obtained;
[0077] Embodiment 3
[0078] In parts by weight, the raw materials are composed as follows:
[0079]
[0080] The specific preparation process is:
[0081] (1) dispersing 5 of acrylic acid, 8 of styrene, 35 of butyl acrylate, 10 of methyl methacrylate, 2 of methacryloxytrimethoxysilane, 2 of isobutoxyacrylamide, 2 of allyl polyoxyethylene sulfonate, 2 of vinyl polyether, and 50 of water at a speed of 3000 r / min for 2 minutes to obtain a stable emulsion which is pumped into a high-level tank 1;
[0082] (2) Place the polymerization kettle in a constant temperature water bath at 82°C, add 2% ammonium bicarbonate and 100% water into the kettle.
[0083] (3) Dissolve 0.6% ammonium persulfate in 50% water and put it into the high-level tank 2
[0084] (4) Add the monomers in high-level tanks 1 and 2 to the polymerization kettle at the same time. Add the raw materials in high-level tank No. 1 at a uniform speed for 30 minutes. Stop adding the raw materials in high-level tank No. 2 after half of the raw materials are added. Keep warm for 30 minutes.
[0085] (5) Mix 5% acrylic acid, 5% acrylonitrile, 5% acrylamide, 5% isobutyl acrylate, and 1% methacryloyloxytrimethoxysilane, and pump them into the No. 1 high-level tank. At the same time, add the raw materials of the No. 1 and No. 2 high-level tanks at a uniform rate. After 30 minutes, the No. 1 high-level tank is completely dripped, and one quarter of the material remains in the No. 2 high-level tank. After the dripping, keep warm for 30 minutes.
[0086] (6) Mix the remaining raw materials together and pump them into high-level tank No. 1. At the same time, add the raw materials from high-level tanks 1 and 2 dropwise at a uniform rate. The addition should be completed within 30 minutes.
[0087] (7) Immediately raise the temperature to 88°C and keep it warm for 0.5 h;
[0088] (8) Cooling to 40° C., slowly adding 12% sodium hydroxide and 50% water to prepare an emulsion, adding the mixture over 10 minutes, stirring for 30 minutes, and obtaining a triple core-shell emulsion with excellent performance.
[0089] The obtained emulsion had a solid content of 33% and a consistency of 230 cps.
[0090] Embodiment 4
[0091] In parts by weight, the raw materials are composed as follows:
[0092]
[0093]
[0094] The specific preparation process is:
[0095] (1) dispersing 2% acrylic acid, 5% acrylonitrile, 2% hydroxyethyl acrylate, 10% styrene, 25% isooctyl acrylate, 1% allyl phthalate, 2% isobutyloxy acrylamide, 1% allyl polyoxyethylene sulfonate, 4% vinyl polyether, and 50% water at a speed of 3000 r / min for 2 minutes to obtain a stable emulsion, which is pumped into a high-level tank 1;
[0096] (2) Place a polymerization kettle in a constant temperature water bath at 82°C, add 2% acrylic acid, 5% acrylamide, 1% vinyl polyether, 2% ammonium bicarbonate and 100% water into the kettle;
[0097] (3) Dissolve 0.6% ammonium persulfate in 50% water and put it into the high-level tank 2;
[0098] (4) Add the monomers in the header tanks 1 and 2 to the polymerization kettle simultaneously, add the raw materials in header tank 1 at a constant speed over 30 minutes, and stop adding the raw materials in header tank 2 after half of the raw materials are added, and keep warm for 30 minutes;
[0099] (5) Mix the remaining raw materials together and pump them into high-level tank No. 1. At the same time, add the raw materials from high-level tanks No. 1 and 2 dropwise at a uniform rate. The addition will be completed within 30 minutes.
[0100] (6) Immediately raise the temperature to 88°C and keep it for 1 hour;
[0101] (7) Cool down to 40°C, slowly add 1.5% sodium hydroxide and 50% water to form a solution, add it over 10 minutes, stir for 30 minutes, and the obtained emulsion has a solid content of 33% and a consistency of 240 cps.
[0102] Experimental Example 1
[0103] The aqueous electrode edge sealing insulating adhesive prepared in the above embodiment is prepared in the following ratio: boehmite 100, adhesive 330, water 570, and dispersed at high speed to prepare an insulating slurry with a solid content of 20%, which is coated on aluminum foil and copper foil with a scraper and dried to obtain an insulating coating with a thickness of about 20um.
[0104] The performance of the coating layer was tested and the results are as follows:
[0105] Table 1 Performance test results of Examples 1-4
[0106]
[0107] Comparative Example 1
[0108] In this comparative example, based on Example 1, only the acrylic acid content was changed to examine its effect on the performance. The results are shown in the following table:
[0109] Table 2 Effect of acrylic acid content on performance
[0110]
[0111] Comparative Example 2
[0112] This comparative example is based on Example 1, and only the type and amount of the cross-linking agent are changed to examine its effect on the performance. The results are shown in the following table:
[0113] Table 3 Effect of crosslinking agent type and dosage on performance
[0114]
[0115] Result analysis: A single cross-linking agent has major defects in balancing adhesion, electrolyte resistance and toughness, and it is difficult to meet comprehensive performance requirements. The composite cross-linking system can make full use of the characteristics of each cross-linking agent to achieve the best bonding effect.
[0116] Comparative Example 3
[0117] This comparative example is based on Example 1, and only the amount of isooctyl acrylate is changed to examine its effect on the performance. The results are shown in the following table:
[0118] Table 4 Effect of acrylate content on performance
[0119]
[0120] Result analysis:
[0121] It can be seen from the table above that when the mass content of isooctyl acrylate is within the range of 30-35%, the peel strength is high, the liquid absorption rate is low, and the electrolyte friction resistance is high. The bending brittleness and oil foil adaptability properties meet the requirements.
[0122] The above description is only a preferred embodiment of the present invention, and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this patent can make some changes or modifications to equivalent embodiments of equivalent changes by using the technical content suggested above without departing from the scope of the technical solution of the present invention. The implementation scheme in the above embodiment can also be further combined or replaced. However, any simple modification, equivalent change and modification made to the above embodiment based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the solution of the present invention.
Claims
1. A water-based electrode edge sealing insulating adhesive, characterized in that: It has a core-shell structure with polyacrylic acid and its ester as the core and PAA polymer structure fragments as single or multi-layer shells; it is made of a variety of monomers including acrylic acid, acrylic ester, styrene, polar monomers, self-emulsifying monomers, and cross-linking monomers through core-shell emulsion polymerization; In the prepared water-based electrode edge sealing insulating adhesive, the polar group accounts for 5-30%; the self-emulsifying group accounts for 1-8%.
2. The water-based electrode edge sealing insulating adhesive according to claim 1, characterized in that: The carboxyl group accounts for 5-20% in the prepared water-based electrode edge sealing insulating adhesive.
3. The water-based electrode edge sealing insulating adhesive according to claim 1, characterized in that: The mass proportion of acrylic ester in the prepared water-based electrode edge sealing insulating adhesive is 20-50%, preferably 30-40%.
4. The water-based electrode edge sealing insulating adhesive according to claim 1, characterized in that: The polar monomer is selected from one or more combinations of acrylic acid, acrylonitrile, acrylamide, hydroxy acrylate, hydroxypropyl methacrylate, and vinyl polyether; Preferably, the polar monomer is selected from one or more combinations of acrylic acid, acrylonitrile, acrylamide and hydroxyethyl acrylate.
5. The water-based electrode edge sealing insulating adhesive according to claim 1, characterized in that: The mass proportion of the cross-linking monomer is 3-10%, preferably 6-8%; The cross-linking monomer is selected from at least one of diacetone acrylamide (DAAM) / adipic dihydrazide (ADH), isobutyloxy acrylamide (IBAM), epoxy acrylate, methacryloxytrimethoxysilane, and diallyl phthalate (DAP); Preferably, there are two crosslinking monomers selected from the group consisting of diacetone acrylamide / adipic dihydrazide, a combination of diallyl phthalate and isobutoxy acrylamide, diacetone acrylamide and adipic dihydrazide and epoxy acrylate, or a combination of diallyl phthalate and adipic dihydrazide.
6. The water-based electrode edge sealing insulating adhesive according to claim 1, characterized in that: The self-emulsifying monomer is a sulfonate with a double bond, a carboxylate with a double bond, or a polyether with a double bond; Preferably, the self-emulsifying monomer is at least one of allyl polyoxyethylene sulfonate, acrylate, vinyl polyoxyethylene sulfonate, allyl polyoxyethylene sulfonate, and vinyl polyether; Preferably, the self-emulsifying monomer is selected from at least one of acrylate, allyl polyoxyethylene sulfonate, and vinyl polyether.
7. A method for preparing the water-based electrode edge sealing insulating adhesive according to any one of claims 1 to 6, characterized in that: The steps include: S1. At a preset temperature, a part of acrylate, a part of polar monomer, a part of self-emulsifying monomer, a part of cross-linking monomer and water are emulsified at a high speed, and then emulsion polymerization is performed to obtain a core emulsion A; S2, at a preset temperature, uniformly mix part of polar monomers, part of acrylates, another part of self-emulsifying monomers and another part of cross-linking monomers, and gradually dropwise react in the bottom water with emulsion A as the core to obtain a double-layer structure emulsion B; S3, at a preset temperature, uniformly mix part of the polar monomer, the remaining part of the acrylate, and a small part of the self-emulsifying monomer, and gradually dropwise react in the bottom water with the emulsion B as the core to obtain a three-layer structure emulsion C; The emulsion B or C is post-modulated to obtain a water-based electrode edge sealing insulating adhesive with a double-layer or multi-layer core-shell structure.
8. The method for preparing the water-based electrode edge sealing insulating adhesive according to claim 7, characterized in that: The preset temperature is 75-86°C; The reaction is stirred at the same time, and the stirring speed is 200-1000 rpm.
9. The method for preparing the water-based electrode edge sealing insulating adhesive according to claim 7, characterized in that: The post-treatment in step S2 or S3 includes heat preservation and aging treatment of the target emulsion at 86-90°C for 1-2 hours, then cooling to 40°C for chemical deodorization, and adjusting the pH of the emulsion to 7-7.5 to obtain a water-based electrode edge sealing insulating adhesive.
10. An application of the water-based electrode edge sealing insulating adhesive as claimed in any one of claims 1 to 6, characterized in that: Used for edge sealing and insulation treatment of the unloaded part of the current collector in lithium battery pole pieces.